Fabrication of ZnO/ZnO @ carbon dot as photo anode and Natural dye as photosensitizer for dye sensitized solar cell application - gopal, Andal; Jose, Deepa; ., Sivagnanam (International Journal of Engineering and Technology, 2018)
ZnO/ZnO @ carbon dot was hydrothermally synthesized and deposited on indium tin oxide coated glass substrate by doctor blade method for application as working electrode in dye sensitized solar cell. Environment friendly natural dye extracted from Lawsonia inermis leaves was used as photosensitizer to fabricate DSSC. Structural and optical properties of the synthesized nanoparticles were studied by X-Ray, UV-Vis, FT-IR and PL spectroscopy. The photovoltaic properties of the cell have been studied and the best solar energy conversion efficiency was obtained.Â Â